Priority setting: the importance of incorporating opportunity costs - Norheim Ole Frithjof (BMC, 2012)
Abstract This article is a comment on Ofra Golan and Paul Hansen's framework for health technology prioritization that they suggest could be developed and used by the committee selecting new technologies for Israel's health basket. Although Golan and Hansen should be commended for the innovative way they have started to explore these issues, more work need to be done to take proper account of opportunity costs.